Sleep-Disordered Breathing Exacerbates Muscle Vasoconstriction and Sympathetic Neural Activation in Patients with Systolic Heart Failure. (November 2016) - Lobo, Denise M. L.; Trevizan, Patricia F.; Toschi-Dias, Edgar; Oliveira, Patricia A.; Piveta, Rafael B.; Almeida, Dirceu R.; Mady, Charles; Bocchi, Edimar A.; Lorenzi-Filho, Geraldo; Middlekauff, Holly R.; Negrão, Carlos E.
Abstract : Background—: Sleep-disordered breathing (SDB) is common in patients with heart failure (HF), and hypoxia and hypercapnia episodes activate chemoreceptors stimulating autonomic reflex responses. We tested the hypothesis that muscle vasoconstriction and muscle sympathetic nerve activity (MSNA) in response to hypoxia and hypercapnia would be more pronounced in patients with HF and SDB than in patients with HF without SDB (NoSBD). Methods and Results—: Ninety consecutive patients with HF, New York Heart Association functional class II–III, and left ventricular ejection fraction ⩽40% were screened for the study. Forty-one patients were enrolled: NoSDB (n=13, 46 [39–53] years) and SDB (n=28, 57 [54–61] years). SDB was characterized by apnea–hypopnea index ≥15 events per hour (polysomnography). Peripheral (10% O2 and 90% N2, with CO2 titrated) and central (7% CO2 and 93% O2 ) chemoreceptors were stimulated for 3 minutes. Forearm and calf blood flow were evaluated by venous occlusion plethysmography, MSNA by microneurography, and blood pressure by beat-to-beat noninvasive technique. Baseline forearm blood flow, forearm vascular conductance, calf blood flow, and calf vascular conductance were similar between groups. MSNA was higher in the SDB group. During hypoxia, the vascular responses (forearm blood flow, forearm vascular conductance, calf blood flow, and calf vascular conductance) were significantly lower in the SDB group compared with the NoSDB group ( P <0.01 to all comparisons). Similarly, during hypercapnia, the vascular responses (forearm blood flow, forearm vascular conductance, calf blood flow, and calf vascular conductance) were significantly lower in the SDB group compared with the NoSDB group ( P <0.001 to all comparisons). MSNA were higher in response to hypoxia ( P =0.024) and tended to be higher to hypercapnia ( P =0.066) in the SDB group. Conclusions—: Patients with HF and SDB have more severe muscle vasoconstriction during hypoxia and hypercapnia than HF patients without SDB, which seems to be associated with endothelial dysfunction and, in part, increased MSNA response. Abstract : Supplemental Digital Content is available in the text.